Progress in meeting protein needs of infants and pre-school children : (National Academy of Sciences-National Research Council, 1961)
The food and nutrition board is most grateful to the National Institutes of health for the support and participation of the nutrition study section which made possible this important conference and the opportunity it provides for evaluating the progress made throigh the cooperative efforts of a notable group of workers and organizations, and for glimpsing the areas where further work is needed.